2016
DOI: 10.3346/jkms.2016.31.12.2033
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Fever with Total Mechanical Ventilation Time in Critically Ill Patients

Abstract: This research aims to investigate the impact of fever on total mechanical ventilation time (TVT) in critically ill patients. Subgroup analysis was conducted using a previous prospective, multicenter observational study. We included mechanically ventilated patients for more than 24 hours from 10 Korean and 15 Japanese intensive care units (ICU), and recorded maximal body temperature under the support of mechanical ventilation (MAXMV). To assess the independent association of MAXMV with TVT, we used propensity-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The length of intubation was significantly longer for patients with fever than for those without fever. This result supports the findings of previous studies 29,30 that prolonged use of assisted ventilation after surgery increases fever risk.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The length of intubation was significantly longer for patients with fever than for those without fever. This result supports the findings of previous studies 29,30 that prolonged use of assisted ventilation after surgery increases fever risk.…”
Section: Discussionsupporting
confidence: 92%
“…This result supports the findings of previous studies 29,30 that prolonged use of assisted ventilation after surgery increases fever risk.…”
Section: Discussionsupporting
confidence: 92%
“…The China Critical Care Clinical Trials Group was formed in 2009 to boost research in the world's largest nation [17]. The Japanese and Koreans have co-created the Japan-Korea Intensive Care Study (JAKOICS) Group [18,19]. The Saudi Critical Care Trials Group (SCCTG) has produced several highimpact papers [20][21][22] In addition, the reach of research led by the European Society of Intensive Care Medicine (ESICM) Trials Group, the Australian and New Zealand Intensive Care Society (ANZICS) Clinical Trials Group, the Canadian Critical Care Trials Group (CCCTG), and WFICC has extended to Asia [23][24][25][26][27][28][29][30].…”
Section: Critical Care Researchmentioning
confidence: 99%
“…We revealed that a positive chest X-ray had a 19% impact on reducing the survival rate through the mediating effect of IDF and that IDF mediates the impact of central venous catheter placement. Park (31) reported that fever contributed to pronged mechanical ventilation for critically ill patients. Moreover, prolonged endotracheal intubation may increase the risk of ventilator-associated pneumonia, indicated as a positive chest X-ray (32).…”
Section: Discussionmentioning
confidence: 99%